Edukasi Pola Makan Sehat Mencegah Makanan dan Minuman Mengandung Cemaran Mikroba - Peri Peri; Monica Suryani; Devina Chandra (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
In general, school students buy snacks in the school canteen or street vendors (PKL) around the school. 2 The types of food sold are varied, ranging from healthy snacks to unhealthy snacks so that they can attract students to consume school snacks. Healthy snacks are foods that have sufficient and balanced nutrition and do not contain (contaminated) elements that can harm or damage health. This community service activity aims to educate healthy eating patterns to prevent food and drinks containing microbial contamination at Mariana Catholic High School, Medan. The method used is an educational approach through health counseling, interactive discussions, and demonstrations of hygienic practices, especially correct handwashing techniques and the importance of maintaining personal hygiene and the school environment. This activity was attended by 40 students as participants. The evaluation of the activity focused on one main indicator, namely student participation in hygienic behavior practices as a form of direct application of the material that has been given. The results of the activity showed that all participants (100%) followed the demonstrated hygienic practices, which indicates a very high level of participation and enthusiasm. These findings indicate that educational methods accompanied by hands-on practice are effective in increasing understanding and encouraging the adoption of clean and healthy living behaviors. Community service activities at Mariana Catholic High School in Medan have been shown to increase students' knowledge about the dangers of microbial contamination and the development of hygienic behaviors in daily life. Structured and ongoing education is an effective preventive measure to create a healthy and clean school environment.